Rapid single B cell antibody discovery using nanopens and structured light. Issue 6 (18th August 2019) - Winters, Aaron; McFadden, Karyn; Bergen, John; Landas, Julius; Berry, Kelly A.; Gonzalez, Anthony; Salimi-Moosavi, Hossein; Murawsky, Christopher M.; Tagari, Philip; King, Chadwick T.
ABSTRACT: Accelerated development of monoclonal antibody (mAb) tool reagents is an essential requirement for the successful advancement of therapeutic antibodies in today's fast-paced and competitive drug development marketplace. Here, we describe a direct, flexible, and rapid nanofluidic optoelectronic single B lymphocyte antibody screening technique (NanOBlast) applied to the generation of anti-idiotypic reagent antibodies. Selectively enriched, antigen-experienced murine antibody secreting cells (ASCs) were harvested from spleen and lymph nodes. Subsequently, secreted mAbs from individually isolated, single ASCs were screened directly using a novel, integrated, high-content culture, and assay platform capable of manipulating living cells within microfluidic chip nanopens using structured light. Single-cell polymerase chain reaction–based molecular recovery on select anti-idiotypic ASCs followed by recombinant IgG expression and enzyme-linked immunosorbent assay (ELISA) characterization resulted in the recovery and identification of a diverse and high-affinity panel of anti-idiotypic reagent mAbs. Combinatorial ELISA screening identified both capture and detection mAbs, and enabled the development of a sensitive and highly specific ligand binding assay capable of quantifying free therapeutic IgG molecules directly from human patient serum, thereby facilitating important drug development decision-making. The ASC import, screening, and export discovery workflow on the chip was completed within 5 h, while the overall discovery workflow from immunization to recombinantly expressed IgG was completed in under 60 days.